Disintegration of Free-falling Liquid Droplets, Jets, and Arrays in Air; Microgravity Science and Technology; Vol. 34, iss. 2 - Kuznetsov G. V. Geny Vladimirovich; Zhdanova A. O. Alena Olegovna; Voytkov I. S. Ivan Sergeevich; Strizhak P. A. Pavel Alexandrovich (2022, 2022)
Title screen